BEYOND SCREENS- NETFLIX'S SAGA IN BANGLADESH - Syeda Umme, Sadia (INTI International University, 2023)
Netflix, the globally renowned online streaming service, made its foray into the Bangladeshi market in 2016, offering subscribers access to a vast library of Movies and TV-Series through its diverse plans. Despite the platform's popularity, the number of Bangladeshi subscribers stands at approximately 200,000, a figure steadily increasing each month. However, the absence of a robust tax collection mechanism has left the Bangladeshi government unable to harness the potential revenue stream, estimated at around $21 million annually. This incongruity stems from subscribers predominantly utilizing international credit cards and gift card purchases for subscription payments, contributing to a taxation challenge. In the context of Bangladesh's economic landscape, characterized by a predominantly low-income population, the adoption of paid entertainment services, exemplified by Netflix, encounters resistance. This resistance emanates from concerns about affordability, with a significant portion of the population expressing hesitation to allocate funds for entertainment purposes. Criticisms range from perceived high pricing structures to complexities in payment systems. As the dynamics of entertainment consumption evolve within Bangladesh, this exploration delves into the challenges and nuances surrounding Netflix's presence in a socio-economically diverse landscape.